Enhancement of quality of service (QoS) in IEEE 802.11 - Rasul, Ababakr Ibrahim; Fadhil, Diyar Salah (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Today everyone is living in a gold rush of wireless communication worldwide. If we look around, we will find wireless communication happening everywhere. In our home, small routers are providing us with wireless access to the internet in offices, shopping centers, cafes, universities, and so on. In this article, a mechanism has been introduced by combining service differentiation and packet aggregation in IEEE 802.11-based WMNs. The result is IEEE802.11b is the most reliable standard among all other wireless standards. Changes required in modulation techniques so that their overhead can be decreased and data can travel in more effective and efficient way.